The impact of low back pain and vigorous activity on mental and physical health outcomes in older adults with arthritis - Taylor, Janiece L.; Regier, Natalie G.; Li, Qiwei; Liu, Minhui; Szanton, Sarah L.; Skolasky, Richard L. (Frontiers in Pain Research, 2022)
Background: Nearly 50% of Americans aged 65 and above have been diagnosed with arthritis and an estimated 80% of adults experience low back pain (LBP). Little is known about the experience of LBP in older adults with arthritis and its relationships with mental and physical health. Objective: In this study, we examined the relationships between LBP and four physical and mental health conditions (psychological distress, insomnia, mobility limitations, and self-rated health) in older adults with arthritis in the National Health and Aging Trends Study (NHATS). We also examined whether vigorous exercise mediated the relationships between LBP and these four conditions. Materials and Methods: The data from this study comes from waves five through nine of the NHATS. The sample size ranged from 3,490 to 2,026 across these waves. All variables in this study are based on self-report. We used descriptive analyses including means and standard deviations for continuous variables or frequencies and proportions for demographic data. We used Structural equation modeling (SEM) to examine if vigorous activity mediated the relationship between LBP with the four conditions. Results: The age range of the sample was 65 years of age and older. Among those with back pain 78.53% had no mobility limitations. There was a significant relationship between LBP with insomnia (B = 0.48, p < .001), perceived health status (B = -0.38, p < .0010), and psychological distress (0.67, p < .001). Activity mediated the relationship between LBP and insomnia, psychological distress and physical health in adjusted models. Discussion: The presence of low back pain in older adults with arthritis increases the risk of insomnia, psychological distress, mobility limitations, and poorer self-rated health.